Palynology of Carica and Vasconcellea (Caricaceae) Palinología de Carica y Vasconcellea (Caricaceae) - Lagos Túlio César; Chávez-Servia José Luis; Caetano Creucí María; Sandoval Sierra Claudia Lorena (Acta Agronómica)
Palynology of Carica and Vasconcellea (Caricaceae). The pollen of C. papaya and agreements of Vasconcellea cauliï¬‚ora, V. cundinamarcensis, V. crassipetala, V. goudotiana, V. x heilbornii var. chrysopetala, V. longiï¬‚ora and V. sphaerocarpa collected in the Colombian Coffee Growing Zone, using the technique of acetolisis for optic microscopy and the ï¬xation procedure with glutaraldehide, dehydration and ionization with gold-palade, for scanning electronic microscopy was described. The pollen grains were characterized using descriptors, which include the characters of taxonomic value for pollen identiï¬cation, genetically determined. The most important are the number, position and character of the aperture (NPC) and exine ornamentation and stratiï¬cation. The pollen is of medium size for both genera, tricolporate, zonoaperturate, prolate-spheroid to subprolate, isopolar radial symmetry, tectate, dug, foveolate, with columelas. These characters have demonstrated a great contribution to the taxonomy of Caricaceae because the cluster analysis allowed distinguish very well the two genera. Se describe el polen de C. papaya y accesiones de Vasconcellea cauliï¬‚ora, V. cundinamarcensis, V. crassipetala, V. goudotiana, V. x heilbornii var. chrysopetala, V. longiï¬‚ora y V. sphaerocarpa recolectadas en la Zona Cafetera de Colombia, empleando la técnica de acetólisis para microscopía óptica y el procedimiento de ï¬jación con glutaraldehído, deshidratación e ionización con oro paladio, para microscopía electrónica de barrido (MEB). Se caracterizaron los granos de polen por medio de una lista de descriptores que incluyeron los caracteres de valor taxonómico para identiï¬cación del polen, genéticamente determinados, siendo los más importantes el número, posición y carácter de la abertura (NPC) y la ornamentación y estratiï¬cación de la exina. Para los dos géneros el polen es mediano, tricolporado, zonoaperturado, prolato–esferoidal a subprolato, de simetría radial isopolar, tectado, cavado, foveolado, con columelas. Estos caracteres han demostrado gran aporte a la taxonomía de Caricaceae, ya que el análisis de agrupamiento permitió diferenciar bien a los dos géneros.